Theodore Beza: An Introduction to His Life and Theology. By Donald K. McKim and Jim West. Cascade Companions. Eugene, OR: Cascade Books, 2023 - Bruening, Michael W. (Church history, 2024)
Theodore Beza: An Introduction to His Life and Theology. By Donald K. McKim and Jim West. Cascade Companions. Eugene, OR: Cascade Books, 2023. - Volume 93 Issue 3.